VISUAL IDENTITY AND AUDIENCE ENGAGEMENT: PERSONAL BRANDING STRATEGIES ON INSTAGRAM @DSUGYWEDDINGOFFICIAL - Deana Ermania Rahutami; Dimas Herlambang Putra; Farida Nurfalah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the effectiveness of personal branding strategies implemented by the Instagram account @dsugyweddingofficial within the wedding planning industry. Using a qualitative content analysis approach, the research analyzes Instagram posts focusing on the core elements of personal branding: clarity, specialization, and consistency, as outlined by Montoya (2009). The findings indicate that @dsugyweddingofficial successfully communicates its brand identity through clear messaging, a distinctive wedding theme specialization, and consistent visual presentation and tone. The study highlights the importance of strategic content curation in social media branding and the role of audience engagement in building a credible brand presence. In conclusion, this research emphasizes that personal branding through Instagram can significantly enhance visibility and customer loyalty, particularly when executed with clarity, specialization, and consistency.